Reflective journals to explore struggles and difficulties of novice Japanese EFL university instructors. Issue 1 (2nd January 2020) - Yoshihara, Reiko; Kurata, Ayaka; Yamauchi, Ami
ABSTRACT: This study explored reflective journals of two novice EFL (English as a foreign language) instructors in Japanese universities who completed master's degrees in TESOL (Teaching of English to Speakers of Other Languages) in British universities, returned to Japan, and started to teach EFL in Japanese universities. The study examined what practical difficulties and challenges the instructors faced when they used communicative language teaching (CLT) in their classrooms and how they reflected on their struggles for future teaching through reflective journals. Narrative study was used for this research. Whereas reflective journals were the primary resources for data analysis, we collected multiple data sources to ensure triangulation of the qualitative research methodology. Through the analysis of the data, we found that their struggles with CLT included the students' reluctance to engage in group activities, the instructors' struggles with L1 (first language) use, and the difficulty in striking a balance between course goals, the students' English proficiency and a CLT approach. This study also drew on aspects of the overall reflective practices including reflective journals – issues and consequences that offer insight and assistance to novice university instructors and stand to promote their professional development.